Trends in the fish assemblage structure of two South African transition-zone estuaries : can these trends be linked to climate change? - Midgley, Craig (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
Changes in the fish communities of the Breede and Mbashe estuaries were investigated in relation to the environmental variables that influence the fish assemblages in these systems. The Breede Estuary (34Â° 24'21.6" S, 20Â° 51' 08.2" E) occurs within the warm-temperate/cool-temperate transition-zone, while the Mbashe Estuary (32o 14' 55.4"S, 28o 54' 03.7"E) falls within the subtropical/warm-temperate transition-zone along the South African coastline. The Breede Estuary was sampled (seine and gill nets) during summer (January-March) over a period of 10 years (2002-2012), while the Mbashe Estuary was sampled (seine net) during spring (October) over a period of three years (2010-2012). The proportion of tropical fish species was higher in the Mbashe Estuary compared to the Breede Estuary, while the Breede Estuary contained a higher proportion of temperate species than the Mbashe Estuary. Although the abundance of individual species in both estuaries varied, the ranking of species in the Breede Estuary was stable over the 10 year period. Multivariate analysis showed that the fish communities within each reach (upper, middle, lower) of the Breede Estuary remained similar, regardless of year. In contrast, species composition in the Mbashe Estuary differed significantly between years mainly due to differences in the river flow regime during the study period. Environmental variables responsible for structuring the fish assemblage in each estuary differed. Salinity significantly impacted the spatial fish assemblage structure of the Breede Estuary, with most of the species recorded being associated with the more saline lower reaches. The abundance of tropical species near their distributional limit in the Breede Estuary appeared to be impacted by sea surface temperature (SST) as peak total abundance of these species coincided with the warmest SST, while the lowest total abundance coincided with the coldest annual SST during the study period. The fish assemblage structure in the Mbashe Estuary was impacted by differing freshwater input prior to sampling, with flooding negatively impacting the mean total abundance, species composition and diversity in this system. The variables that influenced the fish assemblage structure of both transition-zone estuaries will be affected by climate change in the future. These variables will, in turn, determine the composition, abundance and diversity of species within these important estuarine systems. In order to measure these impacts with any degree of understanding, long-term studies on the abiotic and biotic (including the ichthyofauna) features of these estuaries are required to interpret climate change trends.
Keywords: Estuarine fishes -- South Africa -- Climatic factors; Fish communities -- South Africa